Description of Changes on C-organic, N also The Growth of Pepper Shrub due to The Application of Vermicompost in a Floating System - Nadhira Ghea Salsabila; Siti Masreah Bernas (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2023)
The development of pepper shrub requires an additional fertilizer, hence the pepper plants were classified as nutrient voracious. This study aimed to describe changes in vermicompost on soil N, C-organic and pepper shrubs growth in a floating system. This study utilize a Randomized Block Design Factorial, with 5 levels of treatment, V0 (0 g/plant), V1 (250 g/plant), V2 (500 g/plant), V3 (750 g/plant), and V4 (1000 g/plant). The results indicate that the Vermicompost treatment has no significant effect to increase soil C-organic and soil N nutrient. With the vermicompost treatment, the highest result for soil C-organic and soil N nutrient was produced by 1000 g vermicompost/plant. The best enhancement in plant N nutrient was produced by 500 g vermicompost/plant. The average value of the best number of leaves produced by 1000 g vermicompost/plant. Some leaves indicate some symptoms of disease caused by the fungus Phytophthora capsici which then at 12 WAP there were three unsuccessful plants. As a conclusion, the application of vermicompost was able to provide nutrients for pepper shrubs, especially for increasing C-organic, N nutrient of soil and plants as well as the plant growth.